(untitled) (BIRDEM Medical Journal, 2022)
Background: Pre-eclampsia is a leading cause of maternal mortality in Bangladesh. The most common problem of the gestational diabetic mother is increased incidence of pre-eclampsia. The aim of the study was to compare the maternal and perinatal outcome of diabetic pregnancy complicated with pre-eclampsia and without preeclampsia. Methods: This was a prospective observational study including 70 gestational diabetes mellitus (GDM) cases with pre-eclampsia and 70 patients with GDM without pre-eclampsia admitted in Obstetrics and Gynaecology Department of BIRDEM General Hospital-2. A detailed history was taken, and relevant data were collected through interview in a structured questionnaire and analyses were done according to objectives of the study. Results: In this study, 82% patients were delivered by Caesarean section in the study group (pre-eclampsia) and 72% patients were delivered by Caesarean section in the control group (p value 0.158). Rate of pre-term delivery was 55% in the studygroup and 32% in the control group (p value <0.001). In the study group percentage of intrauterine growth retardation (IUGR) was 11.4% and in control group proportion of percentage of IUGR was 1.4%. There was oligo-hydramnios in 32% subjects of the study group and 22% of control group (p value 3.32). In the study group 44% babies were low birth weight whereas in control group 8% were low birth weight (p value <0.001). Conclusion: The rates of pre-maturity and low birth weight were significantly higher among patients of GDM with pre-eclampsia in comparison to patients with GDM without pre-eclampsia. BIRDEM Med J 2022; 12(2): 106-110